ZnT8 Deficiency Protects From APAP-Induced Acute Liver Injury by Reducing Oxidative Stress Through Upregulating Hepatic Zinc and Metallothioneins - Su, Wen; Feng, Mingji; Liu, Yuan; Cao, Rong; Liu, Yiao; Tang, Junyao; Pan, Ke; Lan, Rongfeng; Mao, Zhuo (Frontiers in Pharmacology, 2021)
ZnT8 is an important zinc transporter highly expressed in pancreatic islets. Deficiency of ZnT8 leads to a marked decrease in islet zinc, which is thought to prevent liver diseases associated with oxidative stress. Herein, we aimed to investigate whether loss of islet zinc affects the antioxidant capacity of the liver and acute drug-induced liver injury. To address this question, we treated ZnT8 knockout or wild-type control mice with 300 mg/kg APAP or PBS. Unexpectedly, we found that loss of ZnT8 in mice ameliorated APAP-induced injury, accopanied by inhibited JNK activation, reduced hepatocyte death and decreased serum ALT and AST levels. An increase in hepatic GSH was observed corresponding to a decrease in MDA and 4-HNE levels. APAP-induced inflammation and glycogen depletion were also alleviated. In contrast, no significant changes were observed in CYP2E1, the main enzyme responsible for drug metabolism. In addition, elevated levels of hepatic zinc and metallothionein were found, which may contribute to the hepatoprotective effect in ZnT8 knockout mice. Taken together, ZnT8 deletion protects the liver from APAP toxicity by attenuating oxidative stress and promoting hepatocyte proliferation, which may provide new insights to understand the function of ZnT8 and zinc as key mediators linking pancreatic and hepatic functions.